Job Mobility as a New Explanation for the Immigrant-Native Wage Gap: A Longitudinal Analysis of the German Labor Market - Brenzel, Hanna; Reichelt, Malte (International Migration Review, 2018)
In industrialized countries, wages between migrants and natives usually differ. Previous studies that mostly focused on human capital theory and cross-sectional wage differences failed to fully explain the wage gap. We offer a new explanation and assume that differences in the employment trajectories of migrants and natives contribute to diverging wages after labor market entrance. Utilizing longitudinal data for Germany, we analyze the job mobility of migrants and natives and distinguish among voluntary, involuntary, and internal job changes. Indeed, we find evidence for differences in transition patterns and — using several fixed-effects regressions — are able to explain a substantial part of the gap in hourly wages. The results suggest that the higher number of involuntary changes among migrants increases the wage gap. In contrast, support for more voluntary and internal job changes among migrants should help to counteract diverging earnings trajectories.
CRIS-Team Scopus Importer:2023-06-14